Ferulic Acid, But Not All Hydroxycinnamic Acids, Is a Novel T3SS Inducer of Ralstonia solanacearum and Promotes Its Infection Process in Host Plants under Hydroponic Condition - Zhang, Yong; Li, Jing; Zhang, Weiqi; Wang, Rongsheng; Qiu, Qiaoqing; Luo, Feng; Hikichi, Yasufumi; Ohnishi, Kouhei; Ding, Wei (Frontiers in Plant Science, 2017)
Hydroxycinnamic acids (HCAs) are typical monocyclic phenylpropanoids, including cinnamic acid (Cin), coumaric acid (Cou), caffeic acid (Caf), ferulic acid (FA) and their isomers, and involved in the interactions between pathogens and host plants. Here, we focused on the impact of HCAs on expression of type III secretion system (T3SS) in Ralstonia solanacearum. FA significantly induced the expression of the T3SS and some type III effectors (T3Es) genes in hrp-inducing medium, while did not the other HCAs. However, exogenously supplemented FA did not affect the T3SS expression in planta and the elicitation of the hypersensitive response (HR) in tobacco leaves. Consistent with its central roles in pathogenicity, the FA-induced expression of the T3SS led to significant promotion on infection process of R. solanacearum in tomato plants under hydroponics cultivation. Moreover, the FA-induced expression of the T3SS was specifically mediated by the well-characterized signaling cascade PrhA-prhI/R-PrhJ-HrpG-HrpB, independent of the other known regulatory pathways. In summary, our results demonstrated that FA, a novel inducer of the T3SS in R. solanacearum, was able to promote its infection process in host plants under hydroponics condition.